Avoiding the pitfalls of deep learning : solving model overfitting with regularization and dropout (O'Reilly Media, 2017)
"Understanding how to create a deep learning neural network is an essential component of any data scientist's knowledge base. This course covers some of the challenges that arise when training neural networks. It focuses on the problem of overfitting and its potential remedy: regularization."--Resource description page